THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND WORK CULTURE ON JOB SATISFACTION OF STATE SENIOR HIGH SCHOOL 1 PASAWAHAN, PASAWAHAN DISTRICT, KUNINGAN REGENCY - Nuryenda, Endang Yuda; Anugrah, Annisa Putri (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2023)
Low performance is a fundamental problem that can hinder the development of an agency and produce jobs that are not in accordance with expectations. This study aims to determine the effect of organizational climate (X1) and work culture (X2) on performance satisfaction (Y) partially and simultaneously at SMA Negeri 1 Pasawahan, Pasawahan District, Kuningan Regency. This study uses a quantitative method with an associative research design. The sampling technique uses total sampling or saturated samples, with a total of 36 respondents. Data analysis was carried out using multiple linear regression and ANOVA test at a significance level of 0.05. The results showed that organizational climate (X1) has a positive but insignificant effect on performance satisfaction (sig. value 0.000 <0.05). Work culture (X2) has a positive and significant effect on performance satisfaction (sig. value 0.000 <0.05). Simultaneously, organizational climate and work culture have a very significant effect on performance satisfaction (sig. value ANOVA 0.000 <0.05). The resulting regression equation is Y = 2.188 + 0.195X1 + 0.757X2. This study concludes that there is a positive and significant influence between organizational climate and work culture on job satisfaction at SMA Negeri 1 Pasawahan, both partially and simultaneously. Both independent variables, namely organizational climate and work culture, together contribute significantly to increasing teacher job satisfaction.